One-nucleon-induced nonmesonic hypernuclear decay in laboratory coordinates - Galeão, A. P. (2013)
We present a formalism for the computation of one-nucleon-induced nonmesonic weak hypernuclear decay rates in laboratory coordinates, within an independent-particle shell model framework, with a view to its generalization to the case of two-nucleon-induced transitions.